Evaluating the implementation of English communication therapy (ECT): An objective structured clinical assessment (OSCA) approach - W. Widihastuti; Nursanti Dwi Yogawati (Jurnal Penelitian dan Evaluasi Pendidikan, 2019)
This study is aimed at evaluating the implementation of the English Communication Therapy (ECT) instructional program oriented to the Objective Structured Clinical Assessment (OSCA) for the students of the D-3 Nursing Study Program at STIKES Al-Irsyad Al-Islamiyyah, Cilacap. Three research problems are put forward concerning (1) the fit of the program in terms of the variables context, input, process, and product; (2) obstacles faced by students; and (3) attainment of the ECT learning objectives.  The study is evaluation research using the qualitative and quantitative CIPP model. The research subjects are 168 students of the Nursing Study Program of STIKES Al-Irsyad Al-Islamiyyah. Data were collected using interviews, questionnaires, and documentation. The findings show that (1) evaluation of the four variables of context, input, process, and product shows that ECT can be stated as in the good or fit category; (2) main obstacles faced by students are lack of vocabulary and low level of self-confidence; and (3) students are able to achieve the passing grade of 74 at each station on the competency of English speaking about nursing matters.